Students' expectations about professional higher technical courses: the case of the Bragança’s Higher Agriculture School - Ribeiro, Maria Isabel (2019)
Forms of education for adults have two characteristics in common, namely, voluntary participation and the frequency of a course serving a specific purpose. Although some may make the choice and choose to attend a course for social reasons and others may not know clearly what they want, they all have a purpose in mind and, if they cannot reach it, sooner or later they will leave the course. This research had as objectives to know the student’s expectations about the Professional Higher Technical Course they attend; to perceive which attributes they consider to be most important for their choice; and, to identify the factors that contributed the most to the level of satisfaction with the course. A quantitative and cross-sectional study was developed based on a 62 students sample out a 298 students’ universe. To collect the data, a questionnaire was developed according to the literature. The questionnaire was administered by e-mail and in the classroom, during January to July 2017, after obtaining the authorization from the head of the agriculture school. The data were analyzed using SPSS 23.0 software. The Spearman and Mann-Whitney tests were used at a significance level of 5%. The students had a mean age of 21 years old (SD = 4.25), were equally distributed by gender (50%), lived in households composed with 3 people (44.3%), with a monthly income of up to 1000 € (67.3%). Most students were displaced (54.1%), at a distance equal or greater than 50 km from their residence. The distribution of students, by course, was as follows: Veterinary Care (38.7%); Agricultural Production (24.2%); Food Technology (25.8%); Environmental Management (4.8%); Biotechnology and Innovation (3.2%); Viticulture and Enology (3.2%). About 53.2% of the students attended the first year and 41.7% considered that the course has a reasonable degree of difficulty, requiring a lot of effort and work. Regarding the factors that motivated the choice of the course, the most valued were, in descending order of importance, the love for the area (77.0%), the possibility to continue the studies (36.1%), and the career opportunities (37.1%). Most participants were satisfied (36.1%) or very satisfied (26.2%) with the course. Taking into account the location where the course took place, the results show that, in non-displaced courses, the level of satisfaction was higher than that of displaced courses. On the other hand, in non-displaced courses, the factors that are positively and moderately correlated with the level of satisfaction are: the students' opportunities to acquire theoretical knowledge and practical experience in the field, as well as the availability, support and incentive of teachers. For the rest, the level of satisfaction was positively and strongly correlated with factors as the knowledge and competences of the teachers and the methodologies used in the teaching. So, to improve the working conditions of the displaced courses and to intensify the student/school relationship can contribute to improve students’ loyalty toward the institution and to increase their satisfaction level.